Electrochemical detection of human papillomavirus DNA based on an ultrasensitive electrochemical sensing platform using N-graphene paper - Jia Wang; Juelan Ye; Gang Li (Alexandria Engineering Journal)
Human papillomavirus (HPV) is the primary cause of cervical cancer, a major global health concern affecting women worldwide. Early detection of high-risk HPV genotypes is crucial for timely intervention and reducing disease burden. However, current detection methods often lack sensitivity, speed, or cost-effectiveness, especially in resource-limited settings. This work addresses this critical need by developing an ultrasensitive electrochemical biosensing platform based on nitrogen-doped graphene paper electrodes for quantifying high-risk HPV16 DNA sequences. The N-graphene nanohybrid, fabricated via simple solvothermal treatment of biomass-derived graphene oxide, demonstrated significantly enhanced electrical and electrocatalytic properties compared to undoped graphene. DNA detection was achieved through characteristic oxidation signals of guanine bases, which displayed a wide linear dynamic range (0.5–100 μg/mL), low detection limit (75 pg/mL), and excellent reproducibility (relative standard deviation <3.5 %). Detailed spectroscopic and electrochemical analyses revealed the key roles of pyridinic nitrogen defects in improving interfacial charge transfer kinetics and mitigating biofouling issues. This synergistic combination of high electrical conductivity and versatile surface functionality paves the way for equipment-free, point-of-care genosensor devices tailored for quantitative biomarker screening in resource-constrained environments.